LEARNING OUTCOMES OF SCIENCE SUBJECTS FOR BOARDING SCHOOL AND NON-BOARDING SCHOOL CLASS VIII STUDENTS (COMPARATIVE STUDY OF STUDENTS OF ULUMUL QUR'AN PLUS JUNIOR HIGH SCHOOL AND SMP NEGERI 2 TAPAK TUAN) - Abu Bakar; Akmaluddin; Siti Mayang Sari; Munawar (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Boarding school and non-boarding school system policies affect the potential for learning time for students who are boarded (boarded) to be more. This study aims to determine the comparison of science learning outcomes in class VIII students of Boarding Schools and Non-Boarding Schools. This research uses a quantitative approach with a comparative research type. The samples in this study were 26 students in class VIII B at SMP Plus Ulumul Qur'an and 26 students in class VIII B at SMP N 2 Tapak Tuan. Data collection techniques in the form of documentation of the raw value of learning outcomes. Data analysis techniques using the normality test and t test. The results showed that there was a comparison of science learning outcomes for boarding school and nonboarding school students. Where the lowest science learning outcomes for Boarding School students was 20 and the highest score obtained by students was 84. Where only 4 students met the KKM criteria, while the other students had not been able to complete their learning outcomes. While the lowest nonboarding school student learning outcomes were 44 and the highest scores obtained by students were 88. Where 12 students met the KKM criteria, while the other students had not been able to complete their learning outcomes.